THE CHARACTERISTIC FEATURES OF INTERNET COMMUNICATION - Karen , Kuhel; G‘afurova , Nigora Sa’dullayevna (Innovative Development in Educational Activities, 2024)
Today, the global computer network has become one of the main means of communication between people and the main source of information. The Internet is an association of computer networks with common standards that allow messages to be sent from any Central Computer (or host) on the same network to any other host.